European contract law and the Digital Single Market : the implications of the digital revolution / edited by Alberto de Franceschi. - De Franceschi, Alberto (Intersentia, 2016)
The EU is committed to making the Single Market fit for the digital age, by enhancing the protection of consumers and data subjects, while providing businesses with the legal certainty they need to invest in this field and support growth and innovation. In this context, European Contract Law and the Digital Single Market, an edited collection consisting of carefully selected contributions by leading scholars, addresses the impact of digital technology on European Private Law in light of the latest legislative developments including the EU Regulation of 27 April 2016 on the protection of natural persons with regard to the processing of personal data and on free movement of such data, as well as the European Commission's proposals of 9 December 2015 for a Directive on the supply of digital content, for a Directive on online and other distance sale of goods and for a Regulation on the cross-border portability of online content services in the internal market. The book analyses new and urgent issues in the field of contract, data protection, copyright and private international law: namely the EU approach to personal information as a tradeable commodity and as the object of a fundamental right of the individuals concerned, the protection of consumers' and users' rights in contracts for the supply of digital content and on online and other distance sales of goods, the cross-border portability of online content services, the new features of standard contracts in the digital market and the issues surrounding the emergence of the so called platform economy. Written for both scholars and practitioners, this edited collection provides clear answers to the challenges posed by the digital revolution and acts as a solid basis for further developments of EU law.With contributions by: Christoph Busch, Joana Campos Carvalho, Alberto De Franceschi, Pietro Franzina, Martin Gebauer, Geraint Howells, Peter Kindler, Michael Lehmann, Rodrigo Momberg, Jorge Morais Carvalho, Karl-Nikolaus Peifer, Reiner Schulze, Christian Twigg-Flesner, and Herbert Zech.